Functional Characterization of a Ficolin-mediated Complement Pathway in Amphioxus - Huang, Huiqing; Huang, Shengfeng; Yu, Yingcai; Yuan, Shaochun; Li, Rui; Wang, Xin; Zhao, Hongchen; Yu, Yanhong; Li, Jun; Yang, Manyi; Xu, Liqun; Chen, Shangwu; et al. (The Journal of biological chemistry, 2011)
The ficolin-mediated complement pathway plays an important role in vertebrate immunity, but it is not clear whether this pathway exists in invertebrates. Here we identified homologs of ficolin pathway components from the cephalochordate amphioxus and investigated whether they had been co-opted into a functional ficolin pathway. Four of these homologs, ficolin FCN1, serine protease MASP1 and MASP3, and complement component C3, were highly expressed in mucosal tissues and gonads, and were significantly up-regulated following bacterial infection. Recombinant FCN1 could induce hemagglutination, discriminate among sugar components, and specifically recognize and aggregate several bacteria (especially Gram-positive strains) without showing bactericidal activity. This suggested that FCN1 is a dedicated pattern-recognition receptor. Recombinant serine protease MASP1/3 formed complexes with recombinant FCN1 and facilitated the activation of native C3 protein in amphioxus humoral fluid, in which C3 acted as an immune effector. We conclude that amphioxus have developed a functional ficolin-complement pathway. Because ficolin pathway components have not been reported in non-chordate species, our findings supported the idea that this pathway may represent a chordate-specific innovation in the evolution of the complement system.